Foveal Thickness Fluctuations in Anti-VEGF Treatment for Central Retinal Vein Occlusion - Daisuke Nagasato, MD, PhD; Yuki Muraoka, MD, PhD; Mao Tanabe, MD; Naomi Nishigori, MD; Rie Osaka, MD; Yoshinori Mitamura, MD, PhD; Hitoshi Tabuchi, MD, PhD; Tomoaki Murakami, MD, PhD; Sotaro Ooto, MD; Kiyoshi Suzuma, MD, PhD; Akitaka Tsujikawa, MD, PhD (Ophthalmology Science, 2024)
Purpose: The aim of this study was to examine the effects of foveal thickness (FT) fluctuation (FTF) on 2-year visual and morphological outcomes of eyes with central retinal vein occlusion (CRVO) undergoing anti-VEGF treatment for recurrent macular edema (ME) based on a pro re nata regimen. Design: Retrospective, observational case series. Participants: We analyzed 141 treatment-naive patients (141 eyes) with CRVO-ME at a multicenter retinal practice. Methods: We assessed FT using OCT at each study visit. Patients were divided into groups 0, 1, 2, and 3 according to increasing FTF. Main Outcome Measures: We evaluated the logarithm of the minimal angle of resolution (logMAR) best-corrected visual acuity (BCVA), the length of the foveal ellipsoid zone (EZ) band defect measured using OCT, and the association of FTF with VA and EZ band defect length. Results: The mean baseline logMAR BCVA and FT were 0.65 ± 0.52 (Snellen equivalent range: 20/20–20/2000) and 661.1 ± 257.4 μm, respectively. The mean number of anti-VEGF injections administered was 5.6 ± 3.6. At the final examination, the mean logMAR BCVA and FT values were significantly improved relative to the baseline values (both P < 0.01). During the observation, BCVA longitudinally improved in Groups 0 and 1, remained unchanged in Group 2, and worsened in Group 3. Likewise, the length of the foveal EZ band defect did not increase in Group 0; however, it gradually increased in Groups 1, 2, and 3. Foveal thickness fluctuation was significantly and positively associated with the logMAR BCVA and length of the foveal EZ band defect at the final examination (P < 0.01). The final logMAR BCVA of patients developing neovascular complications was 1.27 ± 0.72 (Snellen equivalent range: 20/50–counting fingers), which was significantly poorer than that of patients without complications (P < 0.001). There was no significant difference in the neovascular complication rate among the FTF groups (P = 0.106, Fisher exact test). Conclusions: In eyes receiving anti-VEGF treatment for CRVO-ME, FTF can longitudinally impair the visual acuity and foveal photoreceptor status during the observation period, thus influencing the final outcomes. However, neovascular complications, which would also lead to a poor visual prognosis, may not be associated with FTF. Financial Disclosures: The authors have no proprietary or commercial interest in any materials discussed in this article.